Kejahatan Pajak Melalui Pencucian Uang Dan Penegakannya - Wahyudi, Wahyudi; Alhadi, Muhammad Daffa (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2025)
Tax crimes accompanied by money laundering are important issues affecting the Indonesian economy. This illegal practice not only costs the country in the form of lost tax revenues, but also disrupts the legitimate financial system and has the potential to damage the integrity of the economy. This article aims to examine forms of tax crimes related to money laundering in Indonesia and assess the effectiveness of law enforcement against these crimes. Using normative legal research methods, this article explores various existing legal regulations and policies, including the Income Tax Law, Money Laundering Law, and other related regulations. The research results show that although Indonesia has a strong legal framework to tackle tax crimes and money laundering, the effectiveness of law enforcement is still hampered by various challenges, such as limited resources, weak institutional coordination, and gaps in the tax system. Therefore, increasing the capacity of law enforcement agencies, the use of advanced technology in detecting suspicious transactions, and increasing international cooperation are very necessary to strengthen law enforcement.